The Relation Between Students’ Frequently in Watching English Content in Social Media and Students’ Vocabulary Mastery - Yadinda Mahardika Darwis Putri; Buhari; Isumarni; Syahrir L; Sam Hermansyah (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study aims to examine the relation between students’ frequency of watching English content on social media and their vocabulary mastery in an English as a Foreign Language (EFL) context. Employing a qualitative descriptive design, this research involved 16 eleventh-grade students of SMA Negeri 2 Sidrap. Data were collected through a vocabulary test and structured interviews. The vocabulary test was used to provide a preliminary description of students’ vocabulary levels, while interviews explored students’ exposure to English content, viewing frequency, and learning experiences outside the classroom. The findings reveal that students who frequently engage with English content on social media platforms such as YouTube, TikTok, and Instagram demonstrate higher levels of vocabulary mastery compared to those with lower exposure. The frequency of engagement ranged from daily to occasional viewing, with content types including both educational and entertainment materials. Repeated exposure to authentic and contextualized language input was found to contribute significantly to vocabulary acquisition. Furthermore, the study indicates that social media serves as an effective informal learning environment that supports autonomous learning and enhances students’ vocabulary development. These findings suggest that integrating social media-based exposure into language learning strategies can be beneficial in improving students’ vocabulary mastery.